2005
DOI: 10.1890/04-0868
|View full text |Cite
|
Sign up to set email alerts
|

Initial Carbon, Nitrogen, and Phosphorus Fluxes Following Ponderosa Pine Restoration Treatments

Abstract: Southwestern ponderosa pine forests were dramatically altered by fire regime disruption that accompanied Euro‐American settlement in the 1800s. Major changes include increased tree density, diminished herbaceous cover, and a shift from a frequent low‐intensity fire regime to a stand‐replacing fire regime. Ecological restoration via thinning and prescribed burning is being widely applied to return forests to the pre‐settlement condition, but the effects of restoration on ecosystem function are unknown. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 51 publications
(57 reference statements)
8
106
1
Order By: Relevance
“…Our 1-and 2-year post-treatment samples reflect these same overall FFS Network patterns. Kaye et al [6] also maintained that fire alone produced greater short-term (2-year) net nitrification rates than thinning plus fire. Similar to the fire only treatment, fungal populations in the forest floor were reduced, yet neither bacteria in the forest floor or mineral soil populations were affected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our 1-and 2-year post-treatment samples reflect these same overall FFS Network patterns. Kaye et al [6] also maintained that fire alone produced greater short-term (2-year) net nitrification rates than thinning plus fire. Similar to the fire only treatment, fungal populations in the forest floor were reduced, yet neither bacteria in the forest floor or mineral soil populations were affected.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected outcome was that the fire only treatment had no effect on net N mineralization or nitrification, substrate utilization, or enzyme activity. Previously in southwestern ponderosa pine forests, Kaye and colleagues [6,21] found that fire alone increased short-term (2-year) net nitrification rates. Significant differences between SWP and this previous study include a reduction and change in composition of the forest floor prior to prescribed fire, and the relatively small plot sizes (0.25 ha).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations